Potential Use of Bamboo Reinforced Concrete Beams towards Sustainable Construction - Tan, Khye Fang; Chin, Siew Choo; Doh, Shu Ing; Jolius, Gimbun; Mohd Tamizi, Mustafa (World Scientific Publishing, 2017)
Bamboo is a natural resource that has the potential to be a substitute of steel reinforcement in reinforced concrete. This paper presents a study on the mechanical properties of bamboo as well as the behaviour of bamboo-reinforced concrete beams. Six bamboo samples were tested for compressive strength and tensile tests, respectively. In terms of structural properties, three reinforced concrete beams were tested to failure under four-point bending, which includes a control beam, a fully and partially reinforced beams with bamboo. Results of mechanical properties showed that bamboo with nodes has higher capability to be able to resist compressive loading compared to bamboo without node. On the other hand, tensile results revealed that bamboo splint managed to achieve 12.5% of the stress of high yield steel with comparable strain value. Results of structural properties showed that beam reinforced with bamboo can achieve approximately 46% of the beam capacity of the steel reinforced beam. Bamboo reinforced concrete beams failed in a brittle manner under bending with vertical cracks in the tension zone.